Pengaturan Pemungutan Suara Elektronik dalam Mewujudkan Pemilu yang Langsung, Umum, Bebas, Rahasia, Jujur dan Adil di Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The purpose of this research is to analyze E-voting arrangements in organizing elections in Indonesia in accordance with the principles of organizing elections in Indonesia. This research is normative legal research which bases its analysis on applicable laws and regulations that are relevant to the legal issues that are the focus of the research. The research data sources are primary data, secondary data and tertiary data which are then analyzed juridically-qualitatively and presented in descriptive form. The research results show that implementing E-voting can overcome various problems in conventional voting systems, but implementing E-voting in elections in Indonesia faces challenges in terms of the readiness of the government, election organizers (KPU), and community culture. Although E-voting offers efficiency and increased participation, clear regulations are still missing, hindering widespread implementation. The readiness of infrastructure and human resources is also an issue, considering the need for adequate training and technology. In addition, people's cultural tendencies that tend to be skeptical of new technology can influence the acceptance of E-voting. Therefore, a comprehensive study and gradual preparation are needed to optimize the implementation of E-voting.